Alien Mysteries, Conspiracies, and Cover-Ups by Kevin D. Randle - Bullard, Thomas E. (Journal of Scientific Exploration, 2014)
UFOs and conspiracies go together like movies and popcorn, only repeated in ufology and popular culture alike to the point of dreary banality. Here at last is a new and meaningful twist on this well-worn theme. Kevin Randle, who brings a deep knowledge of UFOs to his prolific writings on the subject, turns his attention to harmful conspiracies grown up within ufology rather than imposed on it from without. He surveys a broad range of hoaxes that have undermined the credibility of UFOs, from complete fabrications like the Dropa disks and the Maury Island incident, to honest mistakes pushed along by uncritical or self-promoting persons, like the 1997 Phoenix Lights. Randle's extensive research into Roswell provides him with excellent credentials to challenge the "alien autopsy" fake, the Aztec crash-site claims, and the MJ-12 documents. He probes many of his cases to a depth that reveals both their factual and forensic shortcomings, so the reader comes away with genuine understanding of why these claims lack credibility.